Exposing Islamic Character Values at English for Islamic Studies (EIS) Class - Muzammil, Sa'dulloh (Dinamika Ilmu, 2019)
This descriptive qualitative research aims to describe the selection and usage of English for Islamic studies material based on Islamic character values.  It was conducted at English for Islamic studies class followed by the students of Akhwal As Syakhsiyyah Department, IAIN Pontianak. The results showed that the lecturer chose internet authentic material regarding Islamic character values, and he administered an online readability test to gain a reading passage that fits students' abilities. According to interviews with several students, after reading and discussing passages containing Islamic character values, students felt that such reading materials were beneficial information, and they attempted to behave according to Islamic characters mentioned in the reading passages.